PENGARUH PEMBERIAN PASTA TOMAT TERHADAP JUMLAH SEL BUSA PADA ARKUS AORTAAORTA ARCUS TUNICA INTIMA RATTUS NOVERGICUS STRAIN WISTAR TIKUS DENGAN YANG DIBERI DIET ATEROGENIK - Handayani, Dian; Prijadi, Bambang (Fakultas Kedokteran Universitas Brawijaya, 2007)
In Indonesia, the prevalence of coronary heart disease (CHD) was increased. It currently became the main cause of mortality. Unhealthy dietary pattern as the most determinant of atherosclerosis through the increasingof plasma LDL, will be worsen by the presence of free radical such as reactive oxygen species (ROS) that led to accumulation of atherosclerosis plaques. The negative effects of free radicals can be inhibited by antioxidant. Lycopene is a strong antioxidant that able to neutralize free radicals, especially oxygen derived free radicals. This studyaimed to assess the effect of tomato paste containing lycopne to total foam cells. Lycopene has the role to prevent artericoronaria related to atherosclerosis. The most lycopene source is tomatoproducts. This study was a laboratory-experimental study with randomized control group – post-test design. Twentyrandomly selected rats, divided into 5 treatment groups, group P1 (normal diet treatment), P2 (atherogenic diet treatmen)t, P3 (atherogenic diet and addition 0.01 g/days oftomato pasta treatment, P4 (atherogenic diet and addition 0.02 g/days of tomato pasta treatment,),